Hubungan Antara Pengetahuan Keluarga Tentang Skizofrenia dengan Ketaatan Pengobatan Penderita Gangguan Psikotik Fase Awal di Yogyakarta - , CENDERA MARGAHAYU ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : About 450 million peoples around the world experienced meltal disorder. In Indonesia, prevalence of mental disorder both light and heavy are about 18,5%. Family knowledge about Schizophrenia become one of the factors that influence patient adherence to treatment. Objective : To identify the correlation between family Family Knowledge about Schizophrenia with patient adherence of treatment in early psychosis in Yogyakarta. Method : Cross-sectional data analysis between the period of October 2010 and March 2011. A number of 100 test subjects from RSUP Dr. Sardjito, RSJ Gharasia, RSK Puri Nirmala, RSUD Wates, RSUD Bantul and RSUD Gunungkidul were gathered. Caregivers were evaluated on their knowledge on schizophrenia by using a KAST survey. The degree of treatment regularity was measured using the patientâs medical record. Then a chi square statistical analysis was performed. Result : Bivariate analysis showed that there is a significant correlation between family knowledge about schizophrenia with adherence of treatment of early psychosis. Conclution : There is a significant correlation between family knowledge abot schizophrenia with adherence of treatment in early phase of psychotic disorder.